Surgical treatment of adnexal masses during pregnancy - S A Martynov; L V Adamyan; K I Zhordania; A U Danilov (IP Berlin A.V., 2013)
The issue presents the possibilities of new surgical technologies in treatment of adnexal masses during pregnancy and delivery. Surgical treatment provides an option for preservation of pregnancy and reproductive function. Laparoscopic approach allows to eliminate a disease requiring surgery no negative impact on pregnancy course and fetus health.